HUBUNGAN TEKNIK MENYUSUI DENGAN KEJADIAN REGURGITASI PADA NEONATUS DI PUSKESMAS BALOI PERMAI - Yesi Syahrini; Susanti (Zona Kebidanan: Program Studi Kebidanan Universitas Batam, 2026)
Incorrect breastfeeding techniques, such as breastfeeding with an incorrect position and attachment, can cause problems with the return of breast milk that is drunk because of the large amount of air that enters, causing the baby to experience regurgitation. Objective: to determine the relationship between breastfeeding techniques and the incidence of regurgitation in infants aged 0-1 months at the Baloi Permai Health Center. Method: This study is a Qualitative type with a Cross Sectional approach using the Observation method. Observations are carried out by observing and measuring the variables of the research subjects without intervening. Results: The results of the study showed that most of the breastfeeding techniques were wrong, amounting to (79.1%). Regurgitation in the category of rarely experiencing regurgitation <4x in 1 day was (65.1%). There is a relationship between breastfeeding techniques and the incidence of regurgitation in infants aged 0-1 months at the Baloi Permai Health Center which shows a p value of 0.001 <α 0.05, which means Ha is accepted and Ho is rejected. Conclusion: By applying proper breastfeeding techniques, including proper attachment, correct positioning, ending breastfeeding, and burping after breastfeeding, the incidence of regurgitation can be reduced.. Keywords : Breastfeeding techniques, Regurgitation, Neonates